THE EFFECT OF INFORMATION ASYMETRICITY, INDIVIDUAL MORALITY, AND WHISTLEBLOWING ON ACCOUNTING FRAUD TRENDS - Adhayanti Adhayanti; Marwah Yusuf; Anim Wiyana (Institut Transparansi dan Akuntabilitas Publik (INSPIRING), 2022)
Purpose – This study aims to determine whether information asymmetry, individual mortality and Whistleblowing on the tendency of accounting fraud (Study in Sekecamatan Bontomanai Village, Selayar Islands Regency). Design/methodology/approach – Data analysis technique used is multiple linear regression Findings – Based on the results of hypothesis testing shows that information asymmetry has no significant effect on the thendency of accounting fraud, while Whistleblowing has a significant effect on the trend accounting fraud. Originality – The population in this study were all village officials in the Bontomanai sub-district, Selayar Islands district, which amounted to 10 villages Keywords: Information Asymmetry, Individual Morality, Whistleblowing Paper Type Research Result